2013
DOI: 10.1177/1010539513503869
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Primary Health Care in Low- and Middle-Income Countries

Abstract: Since the publication of the World Health Report 2008, there has been renewed interest in the potential of primary health care (PHC) to deliver global health policy agendas. The WHO Western Pacific Regional Strategy 2010 states that health systems in low- and middle-income countries (LMICs) can be strengthened using PHC values as core principles. This review article explores the development of an evidence-based approach for assessing the effectiveness of PHC programs and interventions in LMICs. A realist revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…29 This emphasises the importance of integration of disease-specific activities into the national health system to ensure that when CHWs are involved in additional projects or trials, this does not detract from their routine PHC activities and an appropriate balance between prevention and treatment is maintained. 13 , 41 , 42 If integration does not occur, too much focus may be put on specific diseases and this can lead to over diagnosis and treatment. 42 , 43 Furthermore, integration has been highlighted as a key way to improve CHW capacity for targeting multiple diseases.…”
Section: Discussionmentioning
confidence: 99%
“…29 This emphasises the importance of integration of disease-specific activities into the national health system to ensure that when CHWs are involved in additional projects or trials, this does not detract from their routine PHC activities and an appropriate balance between prevention and treatment is maintained. 13 , 41 , 42 If integration does not occur, too much focus may be put on specific diseases and this can lead to over diagnosis and treatment. 42 , 43 Furthermore, integration has been highlighted as a key way to improve CHW capacity for targeting multiple diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It indicated that a lack of highly qualified GPs is still a limiting factor in gaining patients’ trust. 18 So the key issue is that most patients do not trust GPs and are not willing to contract with them even though GPs can treat a majority of common diseases. Because there are GPs with higher expertise levels, a fundamental and necessary solution would be to introduce and cultivate higher-quality GPs to gain the trust of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Providing evidence on the importance of addressing systems, a recent systematic review and meta-analysis of QI interventions for diabetes care in rural areas of Organisation for Economic Cooperation and Development countries found that successful QI interventions targeted both the health system and clinicians [ 8 ]. Nevertheless, a review by Rule et al addressing the strengthening of PHC in low- and middle-income countries found no consistent approach for assessing the effectiveness of PHC delivery in those countries [ 9 ].…”
Section: Introductionmentioning
confidence: 99%